OBESITY AND ASSOCIATED FACTORS IN ADULTS - Swarowsky, Inácio (2012)
In the last three decades, it has been observed an increasing prevalence of obese individuals, with the consequent diseases related to this phenomenon appearing. These diseases have chronic non-communicable profile, such as the hypertension, diabetes type 2, dyslipidemia, metabolic syndrome and cancer. The obesity acquires endemic proportions and nowadays it is considered one of the biggest public health problems. The present paper aims to review the main concepts related to obesity, etiology, epidemiology, classification, diagnosis and the contribution of physical exercise as treatment. It was found that obesity is mainly due to the type of lifestyle, including poor diet coupled with sedentary lifestyle. With technological innovations, domestic and mobility comforts, daily physical efforts has decreased, contributing to a higher inactivity of individuals associated with the greater offer of food with high caloric density. Planned management strategies and encouraging physical activity have been effective in the process of reducing obesity and overweight.